Isoflavonoids and phytoestrogens from pueraria candollei var. Mirifica related with appropriate ratios of ethanol extraction - N. Peerakam (2018)
© 2018 Chemical Publishing Co. All Rights Reserved. In the folk wisdom of Thailand, chemical compounds from Pueraria candollei var. mirifica play an important role similar to hormones for post-menopausal women. This study aims to determine the appropriate ratio of ethanol to be used for isoflavonoids and phytoestrogens extraction from Pueraria candollei var. mirifica, subsequently, the development as an obstetric cream. Pueraria candollei var. mirifica collected from Thailand and Vietnam were extracted with ethanol (50, 75 and 95 % v/v). The 95 % of ethanolic extract (S095) contained higher quantities of isoflavonoids and phytoestrogens than other ethanolic extracts. The amount of individual isoflavonoids (mg/g extract) were puerarin (5.012), daidzin (2.278), daidzein (1.886), genistin (0.620) and genistein (0.437) which were analyzed by HPLC. The phytoestrogens (mg/g extract) tested by indirect competitive enzyme-linked immunosorbent assay were miroestrol (1.581) and deoxymiroestrol (0.397). In conclusion, 95 % ethanol revealed the highest potential extraction of isoflavonoids and phytoestrogens for use as active ingredients in the development of obstetric creams for post-menopausal women.